Megakaryocytes of patients with MYH9-related thrombocytopenia present an altered proplatelet formation - Pecci, Alessandro; Malara, Alessandro; Badalucco, Stefania; Bozzi, Valeria; Torti, Mauro; Balduini, Carlo L.; Balduini, Alessandra (Thrombosis and Haemostasis, 2009)
MYH9-related disease (MYH9-RD) is an autosomal-dominant thrombocytopenia caused by mutations of MYH9, the gene for the heavy chain of myosin-IIA. Pathogenesis of thrombocytopenia of MYH9-RD is unknown. Recent studies in mice demonstrated that myosin-IIA is an inhibitor of proplatelet formation (PPF), and suggested that it could be involved in the suppression of PPF exerted by megakaryocyte adhesion to type I collagen, which regulates the timing of platelet release within bone marrow. However, the consequences on PPF of the heterozygous mutations causative of the MYH9-RD have never been investigated. We studied the in-vitro PPF by megakaryocytes obtained from four patients carrying the p.D1424N or the p.R1933X mutations. We demonstrated that MYH9-RD megakaryocytes completely lose the physiologic suppression of proplatelet extension exerted by interaction with type I collagen, thus supporting the hypothesis that a premature platelet release within bone marrow contributes to pathogenesis of MYH9-related thrombocytopenia. Moreover, proplatelets extended by MYH9-RD megakaryocytes presented a significant defect in branching in secondary processes (p=0.001) and formed a significantly lower number of proplatelet tips (p=0.005). Since platelets are assembled at the level of proplatelet tips, this defect could further contribute to pathogenesis of thrombocytopenia of MYH9-RD patients.
Keywords: Inherited thrombocytopenia; MYH9-related disease; myosin-IIA; proplatelet formation